PERAN PEREMPUAN DI BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN DESA DI DESA GUNUNG TUMPENG KEC. SURUH DAN DESA BANTAL KEC. BANCAK KABUPATEN SEMARANG - Hakim, Dimas Luqmanul; ., Kushandajani (Journal of Politic and Government Studies, 2020)
The enactment of Law No. 6 of 2014 concerning Villages became a new spiritfor democracy in the village, which in article 58 paragraph 1 discussed the representation ofwomen in the Village Consultative. Women's participation in village development, especiallyin the policy making process is still very low, where women are still stuck in private matters.In this study using qualitative research, Data collection uses in-depth interviews,uninvolved observation and documentation, and data analysis uses the Creswell data analysisstage.The results of this study indicate on the comparison of the roles of women BPDmembers in village development in the villages of Gunung Tumpeng and Pillow Village,shows that the difference in the number of women BPD members is also one of the factorsthat is less than the maximum activeness of women BPD members in the village developmentprocess, seen from Gunung Tumpeng Village where the majority of BPD members are malemen who make women BPD members less active.The advice given is based on an explanation of the analysis of the role of women inBPD in village development in the villages of Gunung Tumpeng and Bantal villages bymaximizing the participation of BPD Perempuan members, holding special hearings onwomen's issues in the village because new ideas and mental courage in delivering suggestionsare needed. The role of BPD women members is not only related to empowerment, but alsophysical development, and the protection of women and children so that there is no moreomission of acts of violence against women and children.Key Words: BPD, Villages, Development, Women, Participation